Analysis Of Anies Baswedan’s Rhetorical Moves In Lectury On Urban Leadership And Digital Resiliance At The Nanyang Technological University - Dwi Cahyo Pranajaya; Agung Suhadi; Washlurachim Safitri (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
The purpose of this study is to identify and describe the rhetorical moves and to identify the dominant type of rhetorical moves used by Anies Baswedan in his lecture on urban leadership and digital resilience at Nanyang Technological University. This study is designed using a descriptive method. The object of this research is Anies Baswedan. The data collection technique through visual video analysis is carried out by analyzing the visual video and then listening to the spoken language to gain understanding with the aim of obtaining data related to the research. In this study, 37 pieces of data were found in Anies Baswedan's speech. The researcher found that the dominant type of rhetoric used by Anies Baswedan is logos. In this research, logos were found in 15 arguments, followed by pathos in 12 arguments, and finally followed by ethos in 10 arguments. Based on the results of this research, this study can serve as a reference for readers and all communication practitioners through the use of logos, ethos, and pathos. For future researchers, this study can be used as a reference to conduct research using different theories and objects in their research. Keywords: Rhetoric, Logos, Ethos, Pathos.